Time to surgical stabilization of rib fractures: does it impact outcomes? - Joseph D Forrester; Yang Cao; Shahin Mohseni; Babak Sarani; Frank Hildebrand; Ahmad Mohammad Ismail; Maximilian Peter Forssten; Marcelo A F Ribeiro (Trauma Surgery & Acute Care Open)
Objectives Rib fractures are common, morbid, and potentially lethal. Intuitively, if interventions to mitigate downstream effects of rib fractures can be implemented early, likelihood of developing these complications should be reduced. Surgical stabilization of rib fractures (SSRF) is one therapeutic intervention shown to be useful for mitigating complications of these common fractures. Our aim was to investigate for association between time to SSRF and complications among patients with isolated rib fractures undergoing SSRF.Methods The 2016–2019 American College of Surgeons Trauma Quality Improvement Program (TQIP) database was queried to identify patient >18 years with isolated thoracic injury undergoing SSRF. Patients were divided into three groups: SSRF ≤2 days, SSRF >2 days but <3 days, and SSRF >3 days. Poisson regression, and adjusting for demographic and clinical covariates, was used to evaluate the association between time to SSRF and the primary endpoint, in-hospital complications. Quantile regression was used to evaluate the effects of time to SSRF on the secondary endpoints, hospital and intensive care unit (ICU) length of stay (LOS).Results Out of 2185 patients, 918 (42%) underwent SSRF <2 days, 432 (20%) underwent SSRF >2 days but <3 days, and 835 (38%) underwent SSRF >3 days. Hemothorax was more common among patients undergoing SSRF >3 days, otherwise all demographic and clinical variables were similar between groups. After adjusting for potential confounding, SSRF >3 days was associated with a threefold risk of composite in-hospital complications (adjusted incidence rate ratio: 3.15, 95% CI 1.76 to 5.62; p<0.001), a 4-day increase in total hospital LOS (change in median LOS: 4.09; 95% CI 3.69 to 4.49, p<0.001), and a nearly 2-day increase in median ICU LOS (change in median LOS: 1.70; 95% CI 1.32 to 2.08, p<0.001), compared with SSRF ≤2 days.Conclusion Among patients undergoing SSRF in TQIP, earlier SSRF is associated with less in-hospital complications and shorter hospital stays. Standardization of time to SSRF as a trauma quality metric should be considered.Level of evidence Level II, retrospective.